2003
DOI: 10.1161/01.cir.0000103130.33451.d2
|View full text |Cite
|
Sign up to set email alerts
|

Implantable Cardioverter-Defibrillator Therapy for Prevention of Sudden Death in Patients With Arrhythmogenic Right Ventricular Cardiomyopathy/Dysplasia

Abstract: Background-Arrhythmogenic right ventricular cardiomyopathy/dysplasia (ARVC/D) is a condition associated with the risk of sudden death (SD). Methods and Results-We conducted a multicenter study of the impact of the implantable cardioverter-defibrillator (ICD) for prevention of SD in 132 patients (93 males and 39 females, age 40Ϯ15 years) with ARVC/D. Implant indications were a history of cardiac arrest in 13 patients (10%), sustained ventricular tachycardia in 82 (62%), syncope in 21 (16%), and other in 16 (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
190
0
12

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 513 publications
(215 citation statements)
references
References 26 publications
13
190
0
12
Order By: Relevance
“…The first and largest of these studies consisted of 132 patients and was published in 2003 by Corrado et al 10. Similar to our study, the authors reported an annual incidence of VF/VFL of 3.3% per year, which is remarkably similar to the rate of 3.6% per year reported in our study.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The first and largest of these studies consisted of 132 patients and was published in 2003 by Corrado et al 10. Similar to our study, the authors reported an annual incidence of VF/VFL of 3.3% per year, which is remarkably similar to the rate of 3.6% per year reported in our study.…”
Section: Discussionsupporting
confidence: 91%
“…The median age at ICD implantation was 36.5 years. The demographic features of patients undergoing ICD implantation in this study are generally similar to those in prior reports 10, 11, 12, 13, 15, 16, 17, 18, 21. Nevertheless, this study is unique in that only patients who met diagnostic criteria were included, and a greater proportion of our ARVD/C population underwent ICD implantation for primary prevention than has been reported in prior series 10, 11, 12, 13, 16, 17, 18, 21.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In DCM, a family history of SCD/SVT/VF is associated with an increased risk of life‐threatening arrhythmias, a concept well established in other forms of arrhythmogenic cardiomyopathies such as ARVC33, 34 and hypertrophic cardiomyopathy 32, 35. Even though none of our AR‐DCM patients fulfilled new task force criteria of ARVC24 with LV involvement, the potential overlap with desmosomal diseases (ARVC, arrhythmogenic cardiomyopathy, left‐dominant arrhythmogenic cardiomyopathy), considered to be distinct disorders,10 warrants further investigations 36…”
Section: Discussionmentioning
confidence: 97%
“…High-risk groups with an increased risk of SCD should be identified. These include young patients who have had a previous syncopal episode, history of cardiac arrest or ventricular tachyarrhythmia, two or more ARVC genetic mutations, patients having ARVC with LV involvement, and patients with TMEM43 gene missense mutation [2327]. …”
Section: Management Of Arvcmentioning
confidence: 99%